Genetic Diversity and Connectivity of the Vulnerable Species Phengaris nausithous in Palencia (Northern Spain) - Luis Fernando Sánchez-Sastre; Óscar Ramírez-del-Palacio; Pablo Martín-Ramos; María-Ángeles Hernández-Minguillón (Insects)
Habitat fragmentation is one of the most critical threats to species conservation, particularly for those with strict habitat preferences and specialized feeding and reproductive behaviors. In such cases, dispersal is essential for gene flow, playing a significant role in determining metapopulation dynamics and stability. This is precisely the case for many Lepidoptera, such as the dusky large blue butterfly (Phengaris nausithous), whose larvae feed on a single host plant (Sanguisorba officinalis) before completing their life cycle as social parasites of Myrmica ants. In Spain, P. nausithous is a vulnerable species found only in certain areas along the mountainous fringe of the northern plateau. In one of these regions (northern Palencia province), five populations separated by distances ranging from 2 to 40 km were studied using microsatellite markers, along with a control population located 200 km away (Soria province), to assess their genetic structure and population dynamics. The results revealed a lack of connectivity and pronounced genetic structuring in four of the studied populations. Only two populations within the Montaña Palentina Natural Park exhibited clear connectivity, demonstrating high gene flow between them. This could be explained by the availability and stability of S. officinalis patches, which may function as stepping stones. This study confirms the challenges posed by habitat fragmentation but also demonstrates that Phengaris nausithous can maintain gene flow between relatively distant areas. At a local level, the results provide the first evidence that the populations studied within the western part of the Montaña Palentina Natural Park belong to a single metapopulation, which may encompass the entire natural park.